2000
DOI: 10.1080/00220270050116923
|View full text |Cite
|
Sign up to set email alerts
|

Assessment: The engine of systemic curricular reform?

Abstract: We sought to examine empirically the prevailing assumption that changing assessment can leverage curricular reform. This assumption has been signi® cantly con-® rmed by our research for the case of mandated high-stakes assessment. Two studies were conducted in the two most populous Australian states, New South Wales and Victoria. In the ® nal two years of secondary school in both states, courses of study and assessment arrangements are mandated for all schools, including the private sector, by the state' s Boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…One issue is whether the results of large-scale assessment should drive curriculum and instructional reform (Barnes et al 2000). Standings on international assessments of mathematics often drive political and educational agendas and there have been several examples of this in situations in recent years (c.f.…”
Section: Assessments Driving Reformmentioning
confidence: 99%
“…One issue is whether the results of large-scale assessment should drive curriculum and instructional reform (Barnes et al 2000). Standings on international assessments of mathematics often drive political and educational agendas and there have been several examples of this in situations in recent years (c.f.…”
Section: Assessments Driving Reformmentioning
confidence: 99%
“…Indeed, the symbiotic relationship between assessment, on the one hand, and curriculum and pedagogy on the other is well documented (e.g. Barnes, Clarke, & Stephens, 2000;Broadfoot, 1996). The impact of GCSE examinations may be especially strong, considering the high stakes they have not only for students but also, through their use as accountability measures, for teachers and schools.…”
Section: Designing a Methods For Studying Changes In Examinations: A 'mentioning
confidence: 99%
“…8 Some educational effects were impressive: Barnes, Clarke, and Stephens (2000) found that, although this was a school leaving examination for age 18, the kinds of problem-solving it introduced became part of the curriculum throughout secondary schools.…”
Section: Traffic Jammentioning
confidence: 99%